A new method to measure the adhesion capability of the metallic surface under shear loading using a modified Arcan test. Issue 12 (15th October 2018) - Legendre, J.; Créac'hcadec, R.; Gilbert, F.; Jacquet, D.
ABSTRACT: The single lap shear test is considered by carmakers as a standard test to control the adhesion of a bonded assembly. In some special cases, when thin steel surfaces are bonded to a structural toughened epoxy-based adhesive, interfacial failure could occur using this mechanical test. Understanding the contribution of the steel surface on the failure mechanisms using the single lap shear test is complex: heterogeneous distribution of stresses, contributions of edge effects, plasticity of the sheet metal, and stiffness of the specimen. It is very difficult to determine failure criteria using the single lap shear test for the interfaces. This work proposes a new method to measure the adhesion capability of the metallic surface under a well-controlled loading. The method is based on the modified Arcan test in shear loading which is adjusted to steel plates. Three different types of surfaces were characterised experimentally and numerically with different adhesion behaviours regarding their failure patterns. The new modified Arcan test is a suitable test to identify the properties of the interfaces in the bonded assemblies using strain and energy criteria.